2015
DOI: 10.1088/0953-2048/28/2/025013
|View full text |Cite
|
Sign up to set email alerts
|

Transport and pinning properties of Ag-doped FeSe0.94

Abstract: We investigated the superconducting transition and the pinning properties of undoped and Ag-doped FeSe 0.94 at magnetic fields up to 14 T. It was established that due to Ag addition the hexagonal phase formation in melted FeSe 0.94 samples is suppressed and the grain connectivity is strongly improved. The obtained superconducting zero-field transition becomes sharp (with a transition width below 1 K), T c and the upper critical field were found to increase, whereas the normal state resistivity significantly re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 37 publications
3
55
0
Order By: Relevance
“…We demonstrated that a Kohler plot is found for the sample FeSeAg4 in the temperature interval 11K -20K [8]. However, the additional magnetoresistive measurements of this sample at higher temperatures (up to 90 K) show that the Kohler plot fails.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…We demonstrated that a Kohler plot is found for the sample FeSeAg4 in the temperature interval 11K -20K [8]. However, the additional magnetoresistive measurements of this sample at higher temperatures (up to 90 K) show that the Kohler plot fails.…”
Section: Resultsmentioning
confidence: 75%
“…We established that the Ag addition in FeSe 0.94 improves both the intra-and inter-granular superconducting properties and slightly increases the irreversibility field [7]. Further investigations showed [8] that critical temperature, the magnetoresistance, the upper critical field and the activation energy for thermally activated flux flow also increased as a result of 4 wt % Ag doping. This study aims to determine the mechanism of action of silver on the superconducting properties and to optimize its content in the superconducting FeSe 0.94 .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Further, the J c value was increased to 1027 A cm −2 in FeSe tapes made using several‐cores of FeSe wires . Recent studies have also clarified that a small quantity of silver addition in FeSe bulk material will increase the superconducting performance as well as the flux pinning energy, respectively . In order to make reliable and reproducible bulk high performance FeSe material for several industrial applications, a further improvement of the J c is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al reported a large transport J c value of 1.4 × 10 4 A/cm 2 in self field and 4.2 K for the Ba 1 − x K x Fe 2 As 2 tapes with Pb and Ag co-doping where Pb addition could improve the gain connectivity and Ag addition was beneficial to grain growth [20]. It was also found that Ag addition could reduce undesired impurity phase in FeSe 0.94 [21]. Accordingly, chemical addition seems to be a very promising way to improve superconducting properties in iron pnictides.…”
mentioning
confidence: 99%